MONITORING OF THE IMPLEMENTATION OF THE EUROPEAN UNION'S SUSTAINABLE TRANSPORT DEVELOPMENT POLICY REGARDING THE USE OF LOW- AND ZERO-EMISSION FLEET ON THE EXAMPLE OF THE GÓRNOŚLĄSKA-ZAGŁĘBIOWSKA METROPOLIS (POLAND) - Aleksander SOBOTA; Anna GRANÀ; Paulina ŚWIERK; Elżbieta MACIOSZEK (Scientific Journal of Silesian University of Technology. Series Transport)
Nowadays, the majority of society decides to use individual transport for everyday travel, which negatively affects the congestion of cities. Nevertheless, in the transport policy of the European Union, public transport is becoming more and more important, which is reflected in strategic documents in the field of sustainable transport development. The effect of this action is to increase the attractiveness of public collective transport, which will also translate into a reduction in pollutant emissions. This article aims to verify the implementation of the European Union's sustainable transport development policy concerning the use of low- and zero-emission rolling stock in the Upper Silesian and Zagłębie Metropolis. As part of the work, the strategic documents of the European Union in the field of sustainable development of transport were analysed. In addition, the idea of establishing the Upper Silesian-Zagłębie Metropolis in the context of the policy of sustainable transport development was introduced and the public transport system functioning in the area of the Metropolis GZM was characterized.